What happens when grit goes bad? Conceptualizing “dark” grit among sport employees - Brent D. Oja; Samantha L. Jordan (Journal of Applied Sports Management, 2024)
This paper details the complexities of the construct known as “grit” and specifically examines the potential for the positive effects of grit to turn maladaptive or “dark.” Although grit is commonly viewed as a generative construct that helps individuals achieve success and experience well-being, past scholars have suggested there could be a “too much of a good thing” effect whereby the helpful outcomes of grit reach a turning point and become detrimental. We propose that the sport industry is an ideal environment for this phenomenon to occur because the industry has high labor demands, and its employees have a strong passion for sport. When sport employees over engage with their work, they are disposed to the negative outcomes of dark grit, which we propose as burnout and turnover. The paper concludes with an overview of the possible future directions for the study of dark grit among sport employees.
Keywords: passion; human resource management; organizational behavior; workplace dynamics